KESIAPAN GURU DALAM MENGHADAPI TANTANGAN PENDIDIKAN BERBASIS TEKNOLOGI - Dhia Fitriah; Meggie Ullyah Mirianda (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Education is the gateway to a better life by fighting for the smallest things to the biggest things that every human being would normally pass. In every era there is always renewal in the education system. In the 21st century, education is required to be more advanced and easily accessible to all groups. One of them, the creation of